Casting a University‐wide Net: Teaching Sustainability in Germany. Issue 1 (25th May 2016) - Ducate, Lara
Abstract : Due to the connection between Germany and sustainability studies, German Programs are well poised to offer a course on German history, culture, and sustainability to meet the needs of the next generation of students. Interdisciplinary humanities courses that incorporate critical thinking, problem solving, and collaborative learning will help to prepare students for their future careers and form thoughtful leaders of tomorrow who will be engaged in their communities and the environment. This article describes a German sustainability course taught in English that incorporates teaching strategies and goals of the liberal arts, while attracting students from a variety of majors and schools across campus. Examples demonstrate that the course discussions, weekly blog posts, exams, and final projects encouraged students to integrate ideas from a variety of disciplines and engage in critical thinking to support well‐researched opinions regarding sustainability while also considering their role in their communities with an eye on sustainability.